Pengaruh Menu Dan Harga Terhadap Keputusan Pembelian Meeting Package Di Hotel Khas Parapat - Simatupang, Tio Hartati; Marpaung, Hasoloan; Hamdani, Muhammad (Politeknik Pariwisata Medan, 2023)
This study aims to determine whether there is an influence between menu and price on purchasing decisions at Hotel Khas Parapat. The background of this research is competition in sales of meeting packages at hotels which are used as a comparison for guests to msake purchases and it is necessary to make packages thatare appropriate and can meet their needs. The research was conducted on guests of the Khas Parapat Hotel who purchased meeting packages for 30 respondents. The research uses quantitative methods with multiple linear tests, validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, t tests, F tests and coefficient of determination tests (R2). The research first tested the questionnaire with a validity test, there were 16 questionnaire items tested and the results were declared valid on the 16 questionnaire items. The research conducted found that menu variables did not have a partial significant effect on purchasing decisions. From the questionnaire data which was then processed using the SPSS ver 29 software program, it produced an adjustment value of 49.3%, decisions were influenced by purchases by menus and prices, while 50.7% were external influences that were not examined in this study.